Modelling the Micro-Foundations of the Audit Society: Organizations and the Logic of the Audit Trail - Power, Michael (Academy of Management Review, 2021)
We live in an “audit society” in which performance accounting and auditing requirements continue to expand, despite widespread criticism by academics and practitioners alike. Macro-institutional theories are good at explaining why organizations adopt practices whose efficacy is dubious by appealing to the power of their legitimizing and symbolic properties. Yet these theories are less able to explain how adoption happens and why practices of accounting and auditing persist and amplify, despite being objects of critique. This article addresses this puzzle by supplementing macro-institutional explanations of the audit society with a micro-foundational analysis grounded in a process model. The model theorizes the humble notion of the audit trail as a process that not only produces auditable accounts but is also a logic that is formative of organizational actors’ dispositions to reproduce those accounts. The analysis contributes to debates about organizational micro-processes and micro-foundations by proposing that this logic of the audit trail is strongly performative of the conditions of its own reproduction and expansion. In explaining the persistence and amplification of the audit society, the model also shows how accounting and auditing are not inherently value-subverting and may be value-enhancing.